Refurbishing the plasmodesmal chamber: a role for lipid bodies? - Paul, Laju K.; Rinne, Paivi L.; Van Der Schoot, Christiaan (Frontiers in Plant Science, 2014)
Lipid bodies (LBs) are universal constituents of both animal and plant cells. They are produced by specialized membrane domains at the tubular endoplasmic reticulum (ER), and consist of a core of neutral lipids and a surrounding monolayer of phospholipid with embedded amphipathic proteins. Although originally regarded as simple depots for lipids, they have recently emerged as organelles that interact with other cellular constituents, exchanging lipids, proteins and signaling molecules, and shuttling them between various intracellular destinations, including the plasmamembrane (PM). Recent data showed that in plants LBs can deliver a subset of 1,3-β-glucanases to the plasmodesmal (PD) channel. We hypothesize that this may represent a more general mechanism, which complements the delivery of glycosylphosphatidylinositol (GPI)-anchored proteins to the PD exterior via the secretory pathway. We propose that LBs may contribute to the maintenance of the PD chamber and the delivery of regulatory molecules as well as proteins destined for transport to adjacent cells. In addition, we speculate that LBs deliver their cargo through interaction with membrane domains in the cytofacial side of the PM.